2023
DOI: 10.3390/vaccines11020412
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hospitalization and Mortality for Influenza and Other Respiratory Viruses during the COVID-19 Pandemic in the United States

Abstract: Seasonal epidemics of respiratory viruses, respiratory syncytial virus (RSV), influenza viruses, parainfluenza viruses (PIVs), and human metapneumovirus (MPV) are associated with a significant healthcare burden secondary to hundreds of thousands of hospitalizations every year in the United States (US) alone. Preventive measures implemented to reduce the spread of SARS-CoV-2 (COVID-19 infection), including facemasks, hand hygiene, stay-at-home orders, and closure of schools and local/national borders may have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Further, evaluation of COVID-19 and comorbidities has been reviewed by several authors and have found significant associations. Hospitalizations and mortality for other respiratory infections were significantly decreased during the pandemic ( 31 ). The effect of COVID-19 on STEMI ( 32 ) and stoke ( 33 ) outcomes have also been demonstrated, resulting in higher in-patient mortality, length of stay and cost of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Further, evaluation of COVID-19 and comorbidities has been reviewed by several authors and have found significant associations. Hospitalizations and mortality for other respiratory infections were significantly decreased during the pandemic ( 31 ). The effect of COVID-19 on STEMI ( 32 ) and stoke ( 33 ) outcomes have also been demonstrated, resulting in higher in-patient mortality, length of stay and cost of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacological measures to prevent SARS-CoV-2 transmission, such as wearing a facial mask and reducing social contacts, were also effective in preventing other viral respiratory infections in various countries, such as the US 31,32,33 , Finland 7 , Japan 34 , France 35 , Australia 36 , and Brazil 37 . The present study registered a sharp decrease in the MRs of these infections among Brazilian adolescents 10-19 years old in 2021 compared to 2020 when the COVID-19 pandemic hit the country in March.…”
Section: Discussionmentioning
confidence: 99%
“…We also compared the clinical characteristics of children with severe influenza before and after the COVID-19 pandemic. This study was conducted during the COVID-19 pandemic, when various respiratory pathogens, including influenza viruses, showed different epidemiological and clinical characteristics ( 18 ).…”
Section: Discussionmentioning
confidence: 99%